A new classification of mandibular fractures. Issue 1 (January 2022) - Brown, J.S.; Khan, A.; Wareing, S.; Schache, A.G.
Abstract: There is no accepted method of reporting mandibular fracture that reflects incidence, treatment and outcome for individual cases. As most series include anatomical site only for all fractures, the aim was to establish a new method to report fractures based on a systematic review of the literature and an internal audit. The classification proposed is: Class I; condyle, II; angle, IIc; II + condyle, III; body/symphysis, IIIc; III + condyle, IV; multiple fractures not including condyle, IVc; IV + condyle, V; bilateral condyle ± other fracture(s). A total of 10, 971 adult and 914 paediatric cases were analyzed through systematic review, and 833 from the regional audit. Only 32% (14/44) of reported series could be reclassified which, when added to the audit data, showed Class IV was most common (29%), with similar proportions of Class III, Class IIIc and Class II (18–23%). External validation (literature review) in terms of treatment and outcome was non-informative, but the internal validation (audit) demonstrated an increasing requirement for adding maxillomandibular fixation (MMF) to open reduction and internal fixation (ORIF) as class increased. The heterogeneity of data reporting found in the systematic review confirms the need for a classification such as this, likely to enhance comparison of varying management protocols.